Vegetable Oil Blends after Frying and Sample Stored in Different Storage Packs - Shakir Ali2, Kashif Hussain3, M. S Alam4, Anwar Habib5, Hamid Nawaz Khan1*, Jafar Salamat Khan1 (Current Botany, 2011)
The work done in the reporting quarter concerns the micronutrient analysis of the blend in fresh oil samples and in samples stored under different storage conditions in various types of containers and as well as before and after frying. Conjugated dienes, p-anisidine value, specific gravity, copper and iron content of the oil samples under different conditions were also estimated, and the oxidative stability of the oils was determined. In particular the retention pattern of micronutrients, conjugated dienes and p-anisidine values in the blend under various storage conditions in different packs was studied.